Disaster Resilient Villages: a systematic review in social science disciplines - Zitri, Ilham; Amil, Amil; Subandi, Azwar; Pratama, Danur Wenda; Oktriani, Elisa; Akbar, Arya (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Disasters in Indonesia are inevitable. Disasters occur due to unpreparedness for the risks and impacts of hazards. Understanding hazards and disaster risk reduction needs to be socialized to the community in an effort to reduce vulnerability and increase capacity. The community is the party directly affected, physically, mentally, and socially, by loss, damage, and loss due to disasters. This study aimed to analyze Disaster Resilient Villages: a systematic review in social sciences. The research method used in this study is descriptive qualitative. The results of the study showed five significant problems of disaster resilient villages. These problems include Local, Disaster, Community, Management, and Risk. This study also involved disaster resilient villages. This study adds something new to the theory by mapping the idea of disaster-resilient villages and looking for relationships between ideas and other important ideas. This study also provides the following practical steps: (1) villages can use knowledge about disaster resilience to assess their resilience through a comprehensive model. (2). The government can adopt the model to measure disaster resilient villages. (3). As a means for villages to behave resiliently in facing disasters